The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1159/000453269
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temporal Fascia and Pedicle Inferior Turbinate Mucosal Flap on Repair of Large Nasal Septal Perforation via Endoscopic Surgery

Abstract: Background: The repair of large nasal septal perforations (NSPs) is one of the most challenging procedures in nasal surgery. The aim of this prospective clinical study was to determine the efficacy of using a pedicle inferior turbinate mucosal flap combined with temporal fascia to repair a large NSP. Method: Between January 2008 and December 2015, 17 consecutive patients with large NSPs underwent septal perforation repair via an endoscopic approach using a pedicle inferior turbinate mucosal flap combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…21 Xu et al used temporalis fascia reported 100% success rate. 22 In the present study, the clinical follow-up showed that the perforations were successfully closed in 19 of 21 patients (90%) treated with bilateral advancement flaps and anterior maxillary sinus wall as interpositional graft. Although the number of patients and the follow-up periods were limited, the data show that anterior maxillary sinus wall is well tolerated as interpositional graft.…”
Section: Discussionsupporting
confidence: 53%
“…21 Xu et al used temporalis fascia reported 100% success rate. 22 In the present study, the clinical follow-up showed that the perforations were successfully closed in 19 of 21 patients (90%) treated with bilateral advancement flaps and anterior maxillary sinus wall as interpositional graft. Although the number of patients and the follow-up periods were limited, the data show that anterior maxillary sinus wall is well tolerated as interpositional graft.…”
Section: Discussionsupporting
confidence: 53%
“…On the other hand, vascularized flaps, for example, pedicled nasal septal mucosal flaps and inferior nasal concha flaps, 19,24,29,30 and axial pattern flaps in other fields, 31 are known to heal well due to the stable blood supply to the flaps 7,32 . Reconstruction with vascularized flaps has superior treatment outcomes to nonvascularized grafts in terms of closure rates for large mucosal defects and the inhibition of ossification in areas of bone exposured 8,17,24 .…”
Section: Discussionmentioning
confidence: 99%
“…28 A study on a rabbit reconstruction model, using a nonvascularized graft for the skull base defect, reported that the respiratory epithelium, including ciliary cells, in the graft used for reconstruction completely disappeared 48 hours after reconstruction, and the epithelium at the reconstruction site had been replaced with squamous epithelium 3 weeks after reconstruction. 28 On the other hand, vascularized flaps, for example, pedicled nasal septal mucosal flaps and inferior nasal concha flaps, 19,24,29,30 and axial pattern flaps in other fields, 31 are known to heal well due to the stable blood supply to the flaps. 7,32 Reconstruction with vascularized flaps has superior treatment outcomes to nonvascularized grafts in terms of closure rates for large mucosal defects and the inhibition of ossification in areas of bone exposured.…”
Section: Discussionmentioning
confidence: 99%
“…Between challenging surgical conditions and hostile healing environments, operative results have been fraught with variable success rates ranging from 30% to 100%. 4 Numerous techniques have been designed to repair nasal septal perforation—bilateral mucoperichondrial flap repair with interposition graft, 5 staged inferior turbinate flap, 6 acelluar dermis interposition graft, 7 auricular cartilage interposition, 8 facial artery myomucosal (FAMM) flap, 9 and interposition grafting with synthetic 4,10,11 and autologous grafts. 12 In addition to operative technique, other contributing factors to successful closure and symptom resolution include the etiology of the septal perforation and the diameter, with perforations greater than 20 mm displaying higher failure rates.…”
Section: Introductionmentioning
confidence: 99%